(untitled) (JIP Jurnal Ilmiah PGMI, 2025)
The use of learning media is one of the tools to help educators achieve their learning objectives. This study aims to develop valid, practical, and effective letter puzzle learning media so that it is suitable for use to improve the early reading skills of class I B students at State Islamic Elementary School (MIN) Pematang Siantar. This type of research is development research or R&D (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data collection instruments used were observation, interviews, and response questionnaires to 1 teacher and 22 students from class one. Furthermore, the initial reading ability test (pretest and posttest), as well as validation sheets from media and material experts, with qualitative and quantitative descriptive techniques for validation and response data, and the n-gain test to analyze the improvement in early reading skills. The results of the media expert validation showed a score of 90.6% and material 82.6%, which indicated the feasibility of the media. The positive response results from teachers (89.2%) and students (86.2%) showed the practicality and good acceptance of the media. A significant increase in students' early reading ability is evidenced by an n-gain of 0.77 (77%) which is categorized as high or effective. This study concludes that letter puzzle learning media is effective in improving the early reading ability of first grade elementary school students.